Transmission of Carbapenem Resistance Between Human and Animal NDM-Positive Escherichia coli Strains. (August 2022) - Shen, Yingbo; Hu, Fupin; Wang, Yongqiang; Yin, Dandan; Yang, Lu; Chen, Yiqiang; Xu, Chunyan; Li, Jiyun; Jiang, Junyao; Wang, Xueyang; Fu, Yulin; Shao, Dongyan; et al.
Abstract: Although carbapenem use is prohibited in animals in China, carbapenem-resistant Escherichia coli (CREC), especially New Delhi metallo-β-lactamase (NDM)-producing strains, are widely prevalent in food-producing animals. At present, the impact of livestock-associated CREC strains on human populations at the national level is unknown. Here, we conduct a retrospective cross-sectional study to investigate the prevalence of CREC from clinical settings across 22 Chinese provinces or municipalities and analyze anthropogenic factors associated with their presence. We also ascertain the bla NDM and bla KPC abundance among pig and chicken farms and present a detailed genomic framework for CREC of animal and human origin. Overall, 631/29 799 (2.1%) clinical Escherichia coli ( E. coli ) isolates were identified as CREC. Multivariable analysis revealed that being male, an age below 1, an age between 13 and 18, provinces with greater chicken production, and provinces with higher pig production were associated with higher odds of CREC infection. In general, 73.8% ( n = 45/61) of pig farms and 62.2% ( n = 28/45) of chicken farms had a bla NDM abundance of 1 × 10 −5 to 1 × 10 −3 and 1 × 10 −3 to 1 × 10 −2, respectively. Among all the Chinese NDM-positive E. coli ( n = 463) available at the National Center for Biotechnology Information (NCBI), the genomic analysis revealed that bla NDM-5 and IncX3 were the predominant carbapenemase gene-plasmid combination, while a highly homogeneous relationship between NDM-positive isolates from humans and animals was demonstrated at the plasmid and core genome levels. All the findings suggest frequent CREC transmission between humans and animals, indicating that further discussions on the use of antibiotics in animals and humans are needed, both in China and across the globe.